Are individual risky behaviours relevant to healthcare allocation decisions? An exploratory study - Pinho, Micaela (2022)
Purpose The problematic surrounding patients' prioritization decisions are currently at the centre of political leaders' concerns. How to define whom to treat when there are not enough resources to treat everybody is the key question. This exploratory study aims to investigate the views of Bulgarian citizens regarding the relevance of the information concerning eight individual health-related behaviours in priority setting decisions: smoking, excess of alcohol, illegal drug use, overweight/obesity, speed driving, extreme sports practice, unsafe sex and overuse of internet and/or mobile devices. Design/methodology/approach Data were collected through a questionnaire where 322 respondents faced hypothetical rationing dilemmas comprising option pairs of the eight risky behaviours. Descriptive statistics and non-parametric tests were performed to define the penalization of each of the risky behaviours and to test for the association between this penalization and the respondent's health habits and sociodemographic characteristics.